Accelerated Tooth Movement with Orthodontic Mini-Screws - S. Aksakalli; A. Balaban; K. Nazaroglu; E. Saglam (Hindawi Limited, 2017)
This case report outlines the possibility of accelerated tooth movement with the combination of microosteoperforation and mini-screws. A 14-year-old male patient presented Class II malocclusion with maxillary incisor protrusion. Upper first premolars were extracted, and after leveling, accelerated canine distalization started. For pre- and postdistalization times, amount of distalization, periodontal health, and root resorption were assessed. Within the limitations of this case report, micro-osteoperforations with mini-screw have a potential for shortening the treatment time.